(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: Sustainable agriculture and food security are critical for addressing contemporary challenges such as environmental degradation and resource depletion while ensuring equitable food distribution. This paper explores the role of Indian agricultural traditions in promoting these goals. India's rich agricultural heritage, rooted in millennia of adaptation to diverse environments, offers valuable insights into sustainable farming practices. Traditional methods, including organic fertilizers, crop rotation, and water-harvesting techniques, reflect a deep understanding of soil management and ecological balance. By integrating these age-old practices with modern sustainability strategies, there is potential to enhance food security and environmental resilience. This approach not only addresses current global challenges but also preserves cultural heritage, demonstrating how traditional knowledge can inform and enrich contemporary agricultural practices. The intersection of Indian agricultural wisdom with modern sustainability objectives provides a unique perspective on building a more resilient, equitable, and environmentally friendly food system.